A tarefa colaborativa em inglês como língua estrangeira no ambiente virtual - Pinho, Isis da Costa (Universidade do Vale do Rio dos Sinos, 2013)
Research on computer-mediated education suggests that technology has a great potential for the teaching and learning of languages from a collaborative perspective, since it enhances the use of language and multimedia as mediational means of construction and sharing of knowledge. Within this context, a quality language education should exploit digital tools’ potentialities in fostering social interaction, in which the learners are challenged to mobilize and transform their linguistic resources to build knowledge about language while they struggle to make meaning in the foreign language. Thus, this research is a case study that aims to investigate the production of undergraduate students in collaborative tasks in English as a foreign language (EFL) in a virtual environment, focusing on the mediation in the learning process. The theoretical framework used in this study consists of vygotskian sociocultural theory principles of learning, complex systems theory, studies in the area of computers in education, and second language and foreign language acquisition reserch. Participants in this study were undergraduate students of Languages/English from a private university in southern Brazil. The data generation was carried out during three classes in the computer lab designed to complement the discipline of English 3 with a series of oral production collaborative tasks through online multimedia resources and digital tools. For the virtual space it was used PBworks wiki as it enables collaborative interaction and sharing of production among all its users. The collaborative tasks envolved EFL chat discussions of Youtube short videos by the learners in pairs based on comprehension questions over Skype. After each task, the dyads were asked to listen to their recordings and reflect on Skype upon their production, the task, and their learning, a collaborative process that was recorded too. Still, in the end of the three classes students answered a questionnaire designed to investigate their perception on the tasks done and the whole experience of using technology to learn a FL. Data analysis focused on five mediational factors of EFL learning, i. e. collaboration, scaffolding, metatalk, task and technology. The results of the present research point to the benefits of collaborative tasks for EFL learning as they fostered an environment of intense exploration, application and modification of language supported by the joint construction of knowledge from focus on error as an opportunity for production improvement. Moreover, it was observed that the use of technology for language learning allowed students to visualize the educational possibilities of tools and resources used for their future teaching practice. Finally, this research intends to provide data and discussion for the improvement of research in Applied Linguistics, Second and Foreign Language Acquisition and Computer-Mediated Language Learning, adding to studies on collaborative tasks from the perspectives of sociocultural and complex systems theory.
Keywords: Teoria sociocultural; Teoria dos sistemas complexos; Aprendizagem de língua estrangeira; Tarefa colaborativa; Ferramentas digitais; Sociocultural theory; Complex systems theory; Foreign language learning; Collaborative task; Digital tools; ACCNPQ::Lingüística, Letras e Artes::Lingüística